Bioactive Glasses for Soft Tissue Engineering Applications - Miguez-Pacheco, Valentina; Gorustovich, Alejandro A.; Boccaccini, Aldo R.; Roether, Judith (Bioactive Glasses: Fundamentals, Technology and Applications, 2017)
In the last few years the usage of bioactive glasses as scaffolds for soft tissue engineering has been investigated more thoroughly. The reason for the boost in interest is the attractive properties bioactive glasses offer, including bioactivity as well as antibacterial, angiogenic and hemostatic properties. So far, most research efforts have focused on applications for repairing skin and nerve tissue although there have been interesting developments in other fields including lung and intestine, which could potentially benefit a large group of patients. Three review articles on this topic have been published, so this chapter will mainly focus on the latest relevant findings. A great number of patents have been registered for the use of bioactive glass for hard tissue engineering. Recently, however, patents have been filed detailing the use of bioactive glass for soft tissue engineering applications which open the way to marketing bioactive glasses for soft tissue repair. The angiogenic effect of bioactive glasses and their dissolution products is of great interest for tissue engineering applications in general and in particular for soft tissue regeneration and repair. The third part of this chapter will detail the latest research on these angiogenic properties of bioactive glasses.
CRIS-Team Scopus Importer:2022-08-05